Genetic relationships and genome verification of Thai banana cultivars using Random Amplification of Polymorphic DNA (RAPD) markers - THANITA BOONSRANGSOM; CHATTHIDAPHON FUENGHOI; DUANGPORN PREMJET; KUNLAYANEE SUVITTAWAT; KUMROP RATANASUT; KAWEE SUJIPULI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Boonsrangsom T, Fuenghoi C, Premjet D, Suvittawat K, Ratanasut K, Sujipuli K. 2023. Genetic relationships and genome verification of Thai banana cultivars using Random Amplification of Polymorphic DNA (RAPD) markers. Biodiversitas 24: 3758-3765. Edible bananas and plantains, belonging to the family Musaceae, genus Musa, represent one of the most important fruit crops, with an annual production of more than 65 million tons worldwide. Bananas have several hybrid variations since they are descended from the two species Musa acuminata Colla (AA genome) and Musa balbisiana Colla (BB genome). Different morphological traits divide almost hybrid bananas into various genomic groupings. Banana genome categorization and identification, however, have always been challenging issues. This study aimed to assess the genetic relationships and verify the genomes of Thai banana cultivars using random amplification of polymorphic DNA (RAPD) markers. Using the 15 selected RAPD markers, 149 RAPD bands were found, with sizes ranging from 0.2 to 3.2 kb, and 88.6% were polymorphic. Polymorphic information content (PIC) values ranged from 0.18 to 0.42, averaging 0.30. Based on the Jaccard coefficient, the unweighted pair-group method arithmetic average (UPGMA) analysis showed that the banana samples had a similarity range of 0.27 to 1.00 with a mean of 0.56, demonstrating an abundance of viability across six banana genomes. The dendrogram generated from RAPD data revealed that all 18 Musa samples could be divided into two main groups (Group I and II). Three additional subgroups were created for each primary group (A, B, and C). The accurate identification and genetic data on the available genetic resources for bananas will be beneficial for breeding and conservation programs.